Membangun Generasi Berkualitas dengan Keluarga yang Terencana serta Pemeriksaan Kesehatan Gratis: Membangun Generasi Berkualitas dengan Keluarga yang Terencana serta Pemeriksaan Kesehatan Gratis - Putri Kurniawati Putri (Yayasan Ahmad Mansyur Nasirah, 2022)
Family planning is an attempt to measure the number of children and the desired birth spacing of children. Therefore, the Government has launched a program or method to prevent and delay pregnancy. The purpose of the family planning program is to form a small family in accordance with the socio-economic strength of a family by regulating the birth of children in order to obtain a happy and prosperous family that can fulfill their needs and carry out their daily activities. free examination and counseling for the recovery of a disease in the community in Beurandeh Village. The method used the first step: a series of coordination, survey and licensing activities, and procurement of facilities and infrastructure (initial logic). Meeting with the head of Beurandeh village, Masjid Raya sub-district, Aceh Besar district. Second step: setting up a command post, disseminating information, collecting data. Third step: improvement steps when in the field in the form of free inspections and providing information on how to build a quality generation with a planned family. The results obtained in the community service program in Beurandeh Village can be carried out properly and smoothly according to the activity plans that have been prepared, although not all Beurandeh people have the awareness to live a healthy life. This activity received a very good response from the community as evidenced by the activeness and presence of the community to take part in free health check-ups by not leaving the activity/place before the time ended. The conclusion is in conducting free checks on the people of Beurandeh Village and providing knowledge about how to build a quality generation with a planned family., knowing about hypertension, blood sugar, gout, by providing knowledge about health, Beurandeh village people can be more careful in eating food that is too excessive, people can also adjust their diet and exercise to reduce the disease they experience or prevent the disease. Because prevention is better than cure. Suggestion Given that many people are less concerned about health, therefore it is necessary to conduct free health checks to reduce the mortality rate caused by chronic diseases.